2005
DOI: 10.1111/j.1469-8137.2005.01364.x
|View full text |Cite
|
Sign up to set email alerts
|

Mixotrophy in orchids: insights from a comparative study of green individuals and nonphotosynthetic individuals of Cephalanthera damasonium

Abstract: Summary• Some green orchids obtain carbon (C) from their mycorrhizal fungi and photosynthesis. This mixotrophy may represent an evolutionary step towards mycoheterotrophic plants fully feeding on fungal C. Here, we report on nonphotosynthetic individuals (albinos) of the green Cephalanthera damasonium that likely represent another evolutionary step.• Albino and green individuals from a French population were compared for morphology and fertility, photosynthetic abilities, fungal partners (using microscopy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
381
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(418 citation statements)
references
References 42 publications
(81 reference statements)
31
381
2
Order By: Relevance
“…In study sites of France, 78 % of investigated root pieces were colonized by Tuber spp., but other associated fungi also included Sebacinales. Another example of mixotrophy of Cephalanthera damasonium from France, involving Sebacinales among other taxa, has been described by Julou et al (2005). In a comparative study of mixotrophic green and albino Cephalanthera longifolia from Estonia, Abadie et al (2006) also found Sebacina in a chlorophyllous plant.…”
Section: Mycoheterotrophic and Mixotrophic Orchidsmentioning
confidence: 95%
“…In study sites of France, 78 % of investigated root pieces were colonized by Tuber spp., but other associated fungi also included Sebacinales. Another example of mixotrophy of Cephalanthera damasonium from France, involving Sebacinales among other taxa, has been described by Julou et al (2005). In a comparative study of mixotrophic green and albino Cephalanthera longifolia from Estonia, Abadie et al (2006) also found Sebacina in a chlorophyllous plant.…”
Section: Mycoheterotrophic and Mixotrophic Orchidsmentioning
confidence: 95%
“…A third nutritional mode, in which fungi partly subsidize photosynthetic orchids with both organic and inorganic compounds, is termed "partial mycoheterotrophy" or "mixotrophy" (Selosse et al 2004) and accounts for a significant number of forest species (Julou et al 2005;Girlanda et al 2006;Tedersoo et al 2007). Mixotrophy allows plants to colonize shaded habitat like dense forests and to be more or less independent of irradiance .…”
Section: Genetic and Functional Fungal Diversity In Mycorrhizal Symbimentioning
confidence: 99%
“…According to Read (Schulze, 2003) soil respiration decreases about 30% if roots and mycorrhizae are excluded. Julou et al (2005) showed that there are plants that make use of the carbohydrate flow from the root to the mycorrhizae and tap this flow as parasites. Orchids seem to be especially capable of doing this as a basis for survival in the shade.…”
Section: Respirationmentioning
confidence: 99%